2019
DOI: 10.5005/jp-journals-10024-2689
|View full text |Cite
|
Sign up to set email alerts
|

Potential Myogenous Temporomandibular Disorders Following Iatrogenic Occlusal Disturbance: A Pilot Study

Abstract: Aim: There is an inadvertent alteration of the occlusal surface after dental treatment. However, research concerning the effect of these iatrogenic disturbances on the temporomandibular joint (TMJ) is scarce. Hence, the present study aimed to investigate the relationship between sudden iatrogenic occlusal disturbance and its effect on the myogenous temporomandibular disorder (TMD). Materials and methods: A cross-sectional observational study was conducted among 30 female subjects aged 18 years to 38 years who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Complications associated with orthognathic surgery can again be divided into perioperative and postoperative [38,39].…”
Section: Poor Insertion Inadequate Fixation Of Prosthesis Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complications associated with orthognathic surgery can again be divided into perioperative and postoperative [38,39].…”
Section: Poor Insertion Inadequate Fixation Of Prosthesis Componentsmentioning
confidence: 99%
“…However, the approach to treating TMDs as a purely dental problem may fail, as a significant proportion of symptoms reflect medical conditions [25,38], including iatrogenic TMDs [8,[39][40][41]. Sharma et al [17] identified factors that increase the risk of temporomandibular disorders are called "Predisposing factors" and those causing the onset of temporomandibular disorders are called "Initiating factors" and factors that interfere with healing or enhance the progression of the temporomandibular disorder are called "Perpetuating factors."…”
Section: Introductionmentioning
confidence: 99%
“…A fim de mimetizar à sensibilidade aos mastigatórios e ATM promovida pelos procedimentos odontológicos iatrogênicos, modelos experimentais de trauma oclusal pela inserção de coroas metálicas tem sido utilizado (ABDALLA et al, 2019;ALAMIR et al, 2019;CAO, 2022). Porém, os estudos envolvendo a instalação de coroas em resina composta, material mais comum na clínica odontológica, ainda são escassos (ZENTHÖFER et al, 2013).…”
Section: Epidemiologia E Fisiopatologia Da Dor Orofacialunclassified